Constitutional Implications of KPK Leadership Term Changes: Analysis of MK Decision No. 112/PUU-XX/2022 and Ruling Inconsistencies - Prabowo, Romi Galih; Tinambunan, Wahyu Donri (Jurnal Hukum Volkgeist, 2023)
Constitutional Court Decision No. 112/PUU-XX/2022, issued on May 25, 2023, underwent an amendment involving an analysis of Article 29 letter e and Article 34 in Law No. 19 of 2019 concerning the Corruption Eradication Commission (UU KPK) in conjunction with Law No. 30 of 2002. This decision is deemed inconsistent with constitutional principles and has the potential to impact anti-corruption efforts in Indonesia. The amendment provides a comprehensive analysis of the effects of the change in the term of office of the KPK leadership on the stability and performance of the institution, as well as its implications for anti-corruption efforts in Indonesia. The research methodology employed is normative juridical legal research with qualitative analysis of the Constitutional Court Decision and relevant legislation. This study aims to delve into the impact of the change in the term of office of the Chairman of the Corruption Eradication Commission (KPK) through Constitutional Court Decision No. 112/PUU-XX/2022. The research findings indicate significant changes in Article 29 letter e and Article 34 of Law No. 19 of 2019 concerning the Corruption Eradication Commission (KPK). Inconsistencies are observed in the application of the open legal policy concept by the Constitutional Court, particularly regarding the assessment of numerical values in previous rulings. Additionally, the study highlights errors in applying the non-retroactive principle concerning the changes in the term of office for KPK leaders, leading to controversy over the retroactive aspect of legal amendments.